Peri‐urban systems alter trophic niche size and overlap in sympatric coastal bird species - Kimberly A. Lato; Matthew Fuirst; Richard R. Veit; Lesley H. Thorne (Ecosphere, 2023)
Abstract Urban habitats can create empty trophic niche space by providing abundant alternative dietary resources, allowing some generalist species to either shift or expand their trophic niches. Resulting changes to trophic niche size may consequently affect interspecific interactions and competition, although trophic impacts are less clear in peri‐urban systems, where both natural and urban resources are readily accessible to highly mobile species. We combined stable isotope (δ13C, δ15N, δ34S) data with GPS tracking of two sympatric coastal bird species (Larus argentatus, L. marinus) across four study sites on the east coast of the United States, ranging from a study site in New York City (the most populous city in the United States) to less‐urban sites off Massachusetts. We quantified the trophic niche size and trophic niche overlap in three‐dimensional isotopic space and assessed spatial overlap in foraging habitat between species at both peri‐urban and less‐urban study sites. We found that for both species, birds at peri‐urban study sites had significantly larger trophic niches than birds from the less‐urban sites. Furthermore, for study sites where both species occurred, we found that overlap in trophic niche space and foraging habitats between species was lower at the peri‐urban study site than at the less‐urban site. These results suggest that peri‐urban environments may facilitate trophic niche expansion and decrease niche overlap in mobile generalist species, contrasting with previous studies showing increased trophic niche overlap in more isolated urban populations. Following further analysis, we found that trophic niche expansion was facilitated by both within‐ and between‐individual differences in foraging strategies. We posit that peri‐urban environments, particularly along coastal areas, can reduce interspecific competition between sympatric species by providing access to a variety of natural and anthropogenic diet items, especially for highly mobile generalist consumers that can access both natural and urban foraging areas. Research assessing how and at what scale peri‐urban systems influence wildlife is key to understanding how further global urbanization will shape ecosystem structures.